Related Pentacyclic Triterpenes Have Immunomodulatory Activity in Chronic Experimental Visceral Leishmaniasis - Jéssica Adriana de Jesus; Márcia Dalastra Laurenti; Leila Antonangelo; Caroline Silvério Faria; João Henrique Ghilardi Lago; Luiz Felipe Domingues Passero (Journal of Immunology Research)
Leishmaniasis is a neglected tropical disease caused by the flagellated protozoa of the genus Leishmania that affects millions of people around the world. Drugs employed in the treatment of leishmaniasis have limited efficacy and induce local and systemic side effects to the patients. Natural products are an interesting alternative to treat leishmaniasis, because some purified molecules are selective toward parasites and not to the host cells. Thus, the aim of the present study was to compare the in vitro antileishmanial activity of the triterpenes betulin (Be), lupeol (Lu), and ursolic acid (UA); analyze the physiology and morphology of affected organelles; analyze the toxicity of selected triterpenes in golden hamsters; and study the therapeutic activity of triterpenes in hamsters infected with L. (L.) infantum as well as the cellular immunity induced by studied molecules. The triterpenes Lu and UA were active on promastigote (IC50=4.0±0.3 and 8.0±0.2 μM, respectively) and amastigote forms (IC50=17.5±0.4 and 3.0±0.2 μM, respectively) of L. (L.) infantum, and their selectivity indexes (SI) toward amastigote forms were higher (≥13.4 and 14, respectively) than SI of miltefosine (2.7). L. (L.) infantum promastigotes treated with Lu and UA showed cytoplasmic degradation, and in some of these areas, cell debris were identified, resembling autophagic vacuoles, and parasite mitochondria were swelled, fragmented, and displayed membrane potential altered over time. Parasite cell membrane was not affected by studied triterpenes. Studies of toxicity in golden hamster showed that Lu did not alter blood biochemical parameters associated with liver and kidney functions; however, a slight increase of aspartate aminotransferase level in animals treated with 2.5 mg/kg of UA was detected. Lu and UA triterpenes eliminated amastigote forms in the spleen (87.5 and 95.9% of reduction, respectively) and liver of infected hamster (95.9 and 99.7% of reduction, respectively); and UA showed similar activity at eliminating amastigote forms in the spleen and liver than amphotericin B (99.2 and 99.8% of reduction). The therapeutic activity of both triterpenes was associated with the elevation of IFN-γ and/or iNOS expression in infected treated animals. This is the first comparative work showing the in vitro activity, toxicity, and therapeutic activity of Lu and UA in the chronic model of visceral leishmaniasis caused by L. (L.) infantum; additionally, both triterpenes activated cellular immune response in the hamster model of visceral leishmaniasis.